The Effect of Online Learning on University Student’s Health - Idris, Mohd Safiee; Harun, Hairuddin; Palpanadan, Sarala Thulasi; Zaidi, Muhammad Shafiq; Azman, Aida Amira; Wonga, Nor Aini; Mohd Razi, Nur Izzati; Zailani, Zurlaika (Development in Language Studies, 2022)
The recent transmission from face -to face learning to fully online learning method due to the Covid-19 pandemic has created a lot of issues in the education system. One of the issues was the effect on students’ physical and mental health. Although students were expected to obtain the information and knowledge shared by educators, there were many factors that have contributed to the students’ health. Thus, this pilot study was conducted to explore the challenges faced by university students in studying an English course while having online learning. A total of 60 respondents from a technical university in Malaysia participated in this study. A questionnaire was distributed to the respondents via Google Form. The data were analyzed to explore the challenges faced by the respondents. Based on the analysis, it was found that many students were struggling to cope with online distance learning due to unclear instructions, unsupportive family members, part-time jobs, and did not have proper healthcare involvement such as sports or hobbies. The respondents also suggested that having counselling sessions, therapy, and taking medication could help. In addition, some of them also were hopeful of having more understanding educators to guide them properly during the testing time.